The Impact of Weak Land Policies on the Escalation of Communal Conflicts in South Sudan - Jundi, Simon (International Journal of Leadership and Governance, 2025)
Purpose: the purpose of the study is to critically explore the influence of South Sudan's fragmented and inadequate land policy framework on persistent community conflicts. By evaluating structural deficiency and discrepancies within existing policies, the investigation seeks to unearth how these regulatory inadequacies contribute to contest over land resources. Methodology: The study employed a descriptive explanatory survey research design with qualitative and quantitative methods. Employing a secondary research design, it synthesized academic literature, conflict case studies, and court documents from 2020 to 2025 to analyze how policy gaps exacerbate inter-communal violence. Key issues identified include legal pluralism, elite land grabs, returnee land disputes, environmental stress, and tensions between statutory and customary legal systems. A matrix of thematic codes derived from the examined literature served as the foundation for the data collection process, which was based on critical document analysis. In order to extract pertinent information about land policy, conflict causes, legal uncertainty, displacement, and institutional responses, documents and publications were analyzed. Ultimately, to arrive at valid conclusions findings from quantitative data were intersected with in depth qualitative data, secondary sources and case studies. Findings: The Qualitative findings reveal the complex interplay between political patronage, institutional weaknesses, and historical grievances, while quantitative analysis indicates strong statistically significant correlations (r = 0.69 to 0.86) between these factors and conflict intensity. Notably, legal ambiguities and elite land acquisitions emerge as primary conflict drivers, especially in regions with weak enforcement and marginalized customary institutions. Unique Contribution to Theory, Practice and Policy: The study recommends that sustainable peacebuilding necessitates harmonizing legal frameworks, enhancing institutional capacity, implementing inclusive land restitution for returnees, and adopting climate resilience strategies. Recommendations for future research include longitudinal, comparative, and geospatial conflict mapping studies, as well as in-depth analyses of gender dynamics within land disputes.